2002
DOI: 10.1046/j.1440-1827.2002.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 mucin expression in follicular dendritic cells and lymphoepithelial lesions of gastric mucosa‐associated lymphoid tissue lymphoma

Abstract: Membrane-associated mucin MUC1 is expressed in various adenocarcinoma cells and active T lymphocytes. We tried to find out whether MUC1 is expressed in gastric mucosa-associated lymphoid tissue (MALT) lymphoma lesion. MUC1 was not expressed in infiltrating T lymphocytes; however, MUC1 was found on the cell surface of follicular dendritic cells (FDC) of germinal centers and in the epithelial cytoplasm of lymphoepithelial lesion (LEL) of the lymphoma, which were immunohistochemically detected by monoclonal antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The expression and function of MUC1 in respiratory mucosal epithelial cells are well documented (12). MUC1 expression was also found in immune cells such as T lymphocytes and dendritic cells (20, 21). However, whether MUC1 is functionally expressed in macrophages has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and function of MUC1 in respiratory mucosal epithelial cells are well documented (12). MUC1 expression was also found in immune cells such as T lymphocytes and dendritic cells (20, 21). However, whether MUC1 is functionally expressed in macrophages has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, while TNF-α plays a role in MUC1 induction in airway epithelial cells during acute bacterial infection (19), whether it is involved in CS-induced and MUC1-mediated lung cancer development is unknown. Furthermore, it is known that MUC1 is expressed in some immune cells (20, 21), but it is unclear if MUC1 is expressed and functions in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies focused on the role of T-and NK-cells [2,3], but the growing knowledge about the outstanding role of dendritic cells (DC) in the induction and control of immunity [4] has recently shifted the focus. A clear correlation between clinical outcome and tumor infiltration by DC has been demonstrated for solid and hematologic cancers, including colorectal [5], ovarian [6], gastric [7] and non-small cell lung cancer [8], breast carcinoma [9], oral squamous cell carcinoma [10] and mucosa-associated lymphoid tissue gastric lymphoma [11]. Multiple abnormalities have been reported in peripheral blood (PB) dendritic cells from patients with hematologic diseases including a lower number of circulating myeloid and plasmacytoid DC pre-cursors in multiple myeloma patients [12], the reduction of blood DC counts in CML [13] and the cytogenetic abnormalities in AML DC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors of MALT type lymphoma after eradication of HP infection are reported to be an assessment of deep submucosal invasion by endosonography [43], monoclonal B-cell population [5], t(11;18)(q21;q21) translocation [39,44], alteration of p53 gene [22] and CagA+ strains of H. pylori [9,10]. Recently, expression of MUC-1 mucin and its disappearance in GC in MALT type gBL was reported in follicular DC in the reactive lymphoid hyperplasia [55], suggesting that the disappearance of MUC-1 mucin in follicular DC in MALT predicts occurrence of MALT type gBL. This study suggested that iNOS expression in the GC with lymphoma cell colonization and in the glandular epithelial cells is also a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%